Ancestors, kings, and the Dao - Cook, Constance A. (Harvard-Yenching Institute monograph series, 2017)
""Ancestors, Kings, and the Dao outlines the evolution of musical performance in early China, first within and then ultimately away from the socio-religious context of ancestor worship. Examining newly discovered bamboo texts from the Warring States period, Constance A. Cook compares the rhetoric of Western Zhou (1046-771 BCE) and Spring and Autumn (770-481 BCE) bronze inscriptions with later occurrences of similar terms in which ritual music began to b